Parkinsonism and chronic manganese exposure: Pilot study with clinical, environmental and experimental evidence. (2020) - Kissani, Najib; Naji, Yahya; Mebrouk, Yassine; Chraa, Mohamed; Ghanima, Abderrazzak
Abstract: Parkinsonism related to chronic Manganese exposure is notably due to focal lesions of the basal ganglia. Our study focused on epidemiological, clinical, toxicological and experimental aspects of Manganese-induced Parkinsonism in south of Morocco. It is a prospective study concerning the workers and the residents bordering on the 2 mines in the south of Morocco. The results of the study concerned 120 cases divided into 4 groups of patients: G1: 30 cases exposed to different incriminated toxic products, which present Parkinsonian signs, G2: 30 cases healthy and exposed, G3: 30 cases affected with Idiopathic Parkinson's disease, and G4: 30 cases healthy and unexposed (controls). The results from the first mine show that 5.7% of the sample developed Manganese-Induced Parkinsonism and this percentage is slightly higher (4.5%) than the second mine site. Chemical and biological analysis revealed high levels of Manganese. The majority of patients did not improve the clinical signs under L-dopa treatment. The authors underline the gravity of Manganese-induced Parkinsonism and propose a listing of the various exposures as well as a cartography of the regions of risk in Morocco. Highlights: The objective of this study was to update the data about Manganese-Induced Parkinsonism in the South of Morocco. Multidisciplinary study putting together clinicians, biologists, biochemists, and pathologists to map accurately areas of exposure to heavy metals. Specific considerations should be taken concerning miners by improving work conditions and obliging the use of protective equipment. General approach on primary prevention for the population living near the mines in the way to decrease the number of cases.